The gray zone between legitimate and predatory open access scientific publishing - Claudia Alvarado-de la Barrera; Santiago Ávila-Ríos; Gustavo Reyes-Terán (Permanyer, 2024)
Certain open access publishers based on the article processing charges model have found it highly profitable to operate within a gray zone that encompasses both legitimate and predatory publishing practices. In this context, maximum profits can be obtained by adequate combinations of journal acceptance rates and elevated article processing charges. Considering that the gray zone can be particularly challenging to identify and that it poses risks for authors aiming to establish academic carreers, we believe it is important to provide a comprehensive description of it.